Correspondence of the Boston Assessment of Traumatic Brain Injury-Lifetime and the VA Comprehensive TBI Evaluation. Issue 5 (September 2018) - Radigan, Lauren J.; McGlinchey, Regina E.; Milberg, William P.; Fortier, Catherine Brawn
Abstract : Objective: To compare the diagnosis of positive versus negative for mild traumatic brain injury (mTBI) using the Boston Assessment of TBI-Lifetime (BAT-L), a validated forensic clinical interview used to identify TBI in research, to the diagnosis of mTBI in the clinical polytrauma service using the Comprehensive TBI Evaluation (CTBIE). Participants: Operation Enduring Freedom/Operation Iraqi Freedom/Operation New Dawn Veterans who were enrolled in the Translational Research Center for TBI and Stress Disorders longitudinal cohort study and received a CTBIE at a Veterans Health Administration healthcare facility ( n = 104). Main Measures: The BAT-L, CTBIE, and Neurobehavioral Symptom Inventory. Results: There was poor correspondence between the BAT-L and CTBIE mTBI diagnoses (κ = 0.283). The CTBIE showed moderate sensitivity but poor specificity relative to the BAT-L. The agreement did not improve after removing individuals who had failed symptom validity measures, as assessed by the Validity-10 scale of the Neurobehavioral Symptom Inventory. Conclusions: This lack of correspondence highlights the difficulties in diagnosing mTBI in Veterans using retrospective self-report. Future work is needed to establish a reliable and valid method for identifying military mTBI both for the care of our Veterans and for appropriate distribution of benefits.